Rumour and Politics - Coast, David (History compass, 2015)
This article examines the historiography of rumour and its relationship to other disciplines, including psychology and anthropology. It explores the methodological problems of defining rumours and interpreting source material, as well as the limitations of psychological interpretations. It examines the ways in which rumours can allow us to access past mentalities and understand popular and elite politics, also analysing attempts by governments to monitor rumours and what they can tell us about the relationship between the individual and the state. Finally, it explores how the interpretations of rumours shaped, and were shaped by, race, gender, social differences and cultural attitudes. Although social scientists and historians have approached the study of rumour in very different ways, closer collaboration between the two can illuminate our understanding of this complex and fascinating phenomenon.